Agreement Analysis of Energy and Protein Contents during Medical Nutrition Therapy at Sanglah Hospital Denpasar - Putu Ayu Laksmini; Ni Made Sri Nopiyani; I Wayan Weta (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Medical nutrition therapy at Sanglah Hospital, Denpasar consists of diet prescription, food labelling, food portion, and food serving. Nutrition assessment has been carried out based on the minimum service standards of Sanglah Hospital Denpasar in 2013, but agreement assessment of energy and protein contents has never been performed in the provision of medical nutrition therapy. The study was conducted to determine the compatibility of energy and protein contents of the diet prescription until the food is served in hospitalized patients who received medical nutrition therapy at Sanglah Hospital Denpasar. Methods: This is a cross-sectional study involving 50 samples of food served with prescribed diet by clinical nutrition specialists at Sanglah Hospital selected by consecutive sampling. Data were collected using observation sheets filled by surveyors and analyzed using Bland Altman Test. Results: There was compatibility of the contents of energy and protein in the provision of medical nutrition therapy of diet prescription with food labelling (energy r=0.43; p=0.04, protein r=0.48; p=0.02), food labelling with food portion (energy and protein r=1.00; p=0.00), food portion with the food serving (energy r=0.48; p=0.03, protein r=0.50; p=0.01), and from diet prescription until the food is served (energy r=0.52; p=0.04, protein r=0.57; p=0.02). Although there is a strong agreement, there is mean value difference which is clinically acceptable. Conclusion: Energy and protein content in the prescribed diet until the food is served at Sanglah Hospital were compatible. The medical nutrition therapy is appropriate and should be evaluated continuously to improve the quality of services at the tertiary level.